Synthesis and characterization of Pr2S3 binary compound - Ramírez Sanabria, Alfonso Enrique; Quijano Ortega, Natalia; Gaona Jurado, Sonia (Universidad Pedagógica y Tecnológica de Colombia, 2018)
In the current work it is shown that the synthesis method that consists in direct reaction of praseodymium and sulfur in its elemental form, using heat as a treatment, with relatively low temperatures and reaction time of one week, allows the preparation of Pr2S3 compound, with a purity of about 92%. The respective characterization of resultant materials was carried out using powder XRD, where by it was determined that the thermal treatment used, effectively leads to the binary sulfide of interest, a compound known to be semiconductor.